2013
DOI: 10.4209/aaqr.2012.05.0125
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of Mass Absorption Efficiency of Black Carbon at Urban and Suburban Locations

Abstract: The mass absorption efficiency (MAE) of black carbon (BC) was measured for the ambient aerosols in urban and suburban areas and exhaust plumes from motor vehicles from September 2010 to September 2011 in Xiamen, China. Ambient aerosols, collected on quartz fiber filters, were analyzed for BC loadings using an OC/EC Carbon Aerosol Analyzer and measured for optical attenuations with a laser/LED transmissometer. The MAE of BC in Xiamen shows a large temporal and spatial variability, varying from 0.47 to 5.15 m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Factors contributing to the uncertainty of MAE EC measurement were investigated in our previous work (Wang et al, 2013). The results showed that measurement uncertainty of MAE EC using an 880 nm LED transmissometer and a Semi-Continuous OC/EC Carbon Aerosol Analyzer (Sunset Laboratory Inc.) was 6.9%.…”
Section: Measurements Of Atn and L Ecmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors contributing to the uncertainty of MAE EC measurement were investigated in our previous work (Wang et al, 2013). The results showed that measurement uncertainty of MAE EC using an 880 nm LED transmissometer and a Semi-Continuous OC/EC Carbon Aerosol Analyzer (Sunset Laboratory Inc.) was 6.9%.…”
Section: Measurements Of Atn and L Ecmentioning
confidence: 99%
“…Statistics of MAE EC were then obtained using MAE EC for each data point. Details of the determination of MAE EC can be found in our previous work (Wang et al, 2013).…”
Section: Determination Of Mass Absorption Efficiency Of Elemental Carmentioning
confidence: 99%
See 1 more Smart Citation
“…Residential biomass burning, another contributor in urban areas, has also been targeted with schemes such as the Clean Air Strategy in the UK (DEFRA, 2019) and the EPA's New Source Performance Standards for residential wood heaters as part of the Clean Air Act in the US (EPA, 2020). Owing to the emerging evidence of BC as pollutant of concern here have been a number of short-term studies investigating the role of BC in the Earth's atmosphere and its impact on air quality across the world including in Europe (Becerril-Valle et al, 2017;Reche et al, 2011), Asia (Chen et al, 2014;Wang et al, 2013), and the Americas (Healy et al, 2017;Peralta et al, 2019;Shirmohammadi et al, 2017). However, in order to better understand its spatio-temporal evolution and to ultimately help elucidate and legislate for its impacts on the environment and on human health, it is necessary to establish integrated permanent measuring networks for the production of long-term data sets.…”
Section: Introductionmentioning
confidence: 99%